Reseller relationship portfolio management at O2 - Brennan, Ross, 1957-; Canning, Louise; McDowell, Raymond (London : SAGE Publications Ltd, 2017)
O2 is the customer brand name of one of the biggest mobile phone service providers in the UK. It reported revenues for the financial year ending 31 December 2008 of E14.3 million. In a competitive marketplace like the UK, this case study discusses the challenges and opportunities available in this market.
Originally published in Brennan, R., Canning, L., & McDowell, R. (2014). Reseller Relationship Portfolio Management at O2. Business-to-business marketing (3rd ed., pp. 261264). London: SAGE Publications Ltd. Print. ISBN: 9781446273722.
Description based on XML content.
Keywords: elektronické knihy; electronic books; O2.; Portfolio management -- Great Britain -- Case studies; Cell phones -- Great Britain -- Case studies; Telecommunication systems -- Case studies